Beyond Force: Evaluating Non-Consensual Marriage Under US Law - Lee, Kelsey Elizabeth (Trinity College Dublin. School of Law. Discipline of Law, 2025)
This thesis explores the evolving relationship between consent and marriage law in the United States. While there is much discussion of the so-called "forced marriage" in America, there is no universal definition of forced marriage and almost all legal intervention focuses on racial and religious minorities. In response, this thesis employs Interpretative Policy Analysis to expand the scope of this discourse and explore "non-consensual marriage", a far broader and more nuanced concept than the narrowly defined "forced marriage". This examination starts with a review of the limited research on forced marriage and marital consent, as well as the potential reasons for this myopic focus in the US. Next, the spectrum of non-consensual marriage is explored including where a spouse 1) lacks capacity to consent, 2) gives consent invalidly, or 3) withdraws consent. Finally, it proposes both definitional and legislative changes that will lead to a more comprehensive and concrete landscape on which we can evaluate marriage and consent. The result of this extensive inquiry is the first large-scale evaluation of the meaning and scope of marital consent in the US.
APPROVED
Keywords: marriage; consent; marital consent; forced marriage; child marriage; history of marriage; marriage and mental disability